Safety Improvement for Sea Taxi Association in Doom Island, Sorong City, Southwest Papua (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Most members of the community on Doom Island, also known as Dum Island in Sorong Islands District, Sorong, provide local transportation and tourists by sea taxi. The well-being of passengers and crew is the most critical aspect of water transport. The level of passenger safety assurance for travel between Dum Island and Sorong City, as well as to other islands, still needs to be improved, according to field observations. Observations show that certain shipping conditions often require more attention to load capacity, passenger positions, and the lack of adequate shipping safety equipment. This socialization is expected to raise awareness of providers of maritime transport services for tourism and the importance of safety in all activities of range. Socialization is a method of implementation of PKM programs, with stages of preparation, performance, and evaluation. The providers of maritime transport services for tourists and the population of Dum Island will get comprehensive information on marine safety regulations, together with the procedure of safety tools for instance sockets, sackcloth jackets, and other life-saving equipment. It is intended to increase their awareness and preparedness in the face of emergencies at sea. With a greater understanding of risks and preventive measures, a safer and more sustainable maritime environment can be achieved.